Biology of Citrus butterfly Papilio demoleus L. (Papilionidae: Lepidoptera) - Dharavath, Saicharan; Karabhantanal, Shreeshail; Anand, Vandana; Akash, M P (Indian Journal of Plant Protection, 2022)
A number of insect pests attack citrus plants both in the nurseries as well as in the orchards inflicting heavy economic losses. Some of the most serious pests of citrus include Papilio demoleus L. and P. polytes L. (Citrus caterpillar), Diaphorina citri K. (Citrus psylla), Phyllocnistis citrella Stainton (Citrus leaf miner), Aonidiella aurantii Maskell and (Citrus red scale) and Dialeurodes citri Ash. (Citrus whitefly). Among them P. demoleus L. (Papilionidae: Lepidoptera), commonly known as orange dog, chequered swallowtail, lemon butterfly, is found throughout tropical and subtropical areas of Southern and Southeast Asia (Guerrero et al., 2004). It is a serious insect pest feeding on citrus leaves and blossoms and are a potential threat to citrus nursery stocks and other young citrus trees in Asia and the Middle East (Lewis, 2012).